Fish diversity, distribution and their relationship with environmental variables in Southern Gulf of Mexico. - Torrruco, Daniel; gonzález, Alicia; González, Ángel Torruco (Revista de Biología Tropical, 2018)
The Campeche Sound has a high heterogeneity of habitats, great fish species diversity, and a strong presence of oil and fishing industries. Even though some information of bento-demersal fish of the area is available, this has been focused on some economically important species. This way, our objective of this study was to obtain the ichthyofaunal spatial distribution and its relationship with this study were were to obtain updated information on a complete local fish species spatial distribution and their relationship with environmental elements, this will improve the baseline to evaluate the potential impact of future oil and fishing developments. For this, our approach used a database obtained in 2010, with a capture made in 54 sites with standard shrimp fishing trawls (60 feet long x 1¼ in. mesh size; towing time 30 min, 2 knots; 19 to 600 m depth) in the Campeche Sound. Our data analysis included: dominance, diversity, equity, assemblies, spatial management and a landscape representation of the area. We collected a total of 33 315 fish, of 80 families, 138 genera and 193 species, that corresponded to 2 502 438 kg. The fish classes Chondrichthyes and Actinopterygii predominated. A total of 17 were dominant, associated to sandy and muddy bottoms, although were species of estuarine environments, reef and pelagic habitats. Averaged diversity (H’) was of 3.2 bits/individuals. In decreasing diversity order, the common fish belong to Perciformes (84 species), Pleuronectiformes (23), Scorpaeniformes (15) and Tetraodontiformes (14); in the same way, the higher richness families were Sciaenidae (15 species), Paralichthyidae (12), Carangidae (10), and Triglidae and Synodontidae (7). Most common genuses were Prionotus (6 species), Citharichthys and Sphoeroides (4 each). Per each station, richness varied between 3 and 56 species, with an average weight of 46 kg. Fish assemblage composition was different among habitats and areas, with divergent management strategies. Landscape analysis defines nodules of high density and diversity that corresponded to river mouths, lagoons and reef areas fish assemblages. Of the relation between variables and community descriptors, only the organic carbon was significant for both abundance and biomass, the REDOX for the species richness and the other variables were not important.